Effect of cow's milk treatment with transglutaminase on the composition and quality of yoghurt with particular reference to its biological value - Masoud, M. S.; Youssef, Mervat S.; Hussein, Gehan A.; Fayed, A. E. (2008)
The aim of this study was to evaluate the impact of cow's milk treatment with transglutaminase (TGase) enzyme on the resultant yoghurt attributes with emphasis on the biological properties. Yoghurt was made using milk treated previously with TGase at levels of nil (the control), 250 and 500 units/1 yoghurt milk at 40°C for 2 h. Then,the enzyme was inactivated by heating, inoculated with 2% of freshly activated yoghurt starter culture (YSC), and incubated until complete coagulatiotl.
Includes reference.
Summary in Arabic.
1
Keywords: Milk yield; Yogurt; Amino acids; Blood plasma; Trace elements in nutrition